Pengaruh Live Streaming dan Flash Sale Terhadap Impulsive Buying Dengan Trust Sebagai Variabel Intervening Pada TikTok Shop - Fitria, Lailatul; Pradiani, Theresia; Hanif, Rifki (JPEK: Jurnal Pendidikan Ekonomi dan Kewirausahaan, 2025)
The rise of social commerce such as TikTok Shop introduces live streaming and flash sale features that potentially trigger impulsive buying. This study aims to examine the effect of live streaming and flash sales on impulsive buying with trust as an intervening variable. A quantitative approach was employed by surveying 100 active TikTok Shop users who had made impulsive purchases within the past year. The sample was selected using purposive sampling, and data were collected through a Google Form questionnaire and analyzed using Structural Equation Modeling–Partial Least Square (SEM-PLS) with SmartPLS 3.0. The results reveal that live streaming, flash sales, and trust significantly and positively affect impulsive buying. Furthermore, live streaming and flash sales significantly influence trust, while trust mediates the relationship between live streaming and flash sales with impulsive buying. These findings highlight the essential role of consumer trust in enhancing the impact of live streaming and flash sale strategies. This study offers practical implications for e-commerce managers to optimize interactive promotional strategies and build consumer trust to increase impulsive purchases.